YOUNG PEOPLE WITH UNLIMITED OPPORTUNITIES - Ahmedova Nilufar Ma`murjonovna (International Engineering Journal For Research & Development, 2020)
At present, at the initiative of the President, systematic work is being carried out in our country to educate the younger generation, to encourage them to grow in all respects, physically healthy, intellectually gifted, spiritually harmonious, in accordance with their work and achievements. At the same time, it is no exaggeration to say that a wide range of opportunities is being created for young people with disabilities in all areas. In this article we will talk about the wide range of conditions created for our young people with disabilities today.